DFT study on the C(N)-NO reaction with isolated and contiguous active sites. (1st September 2017) - Zhang, Hai; Liu, Jiaxun; Wang, Xiaoye; Luo, Lei; Jiang, Xiumin
Abstract: The C(N)-NO reactions with isolated and contiguous active sites leading to the release of N2 are determined by density functional theory (DFT) calculations. Possible transition states and intermediates involved in these reactions are characterized because these influence the directed conversion of C(N) to N2 . The thermodynamic results encompassing these processes are obtained, and they are used as a good candidate to distinguish the difference in reaction mechanism. The contiguous active sites are more favorable than the isolated active site for chemisorption but less favorable for N2 separation due to the large coulomb attractive force. The overall N2 separation from carbonaceous surface with contiguous active sites can take place with the largest energy penalty of 209.6 kJ/mol and an exothermicity of 436.5 kJ/mol. Energetically, the C(N)-NO reactions with isolated active site are also possible where an energy of 410.5 kJ/mol will release and 219.0 kJ/mol energy barrier is required. According to our calculated results, contiguous active sites responsible for surface migration and rearrangement are important in C(N)-NO reactions. Further comparisons with the published works indicate that the N2 separation is dependent on (1) the location of the active site, (2) the form of surface nitrogen and (3) the nearby groups.